A legal study on the laws regulating child marriage among Muslim girls in Malaysia / Nur Saufiah Mohd Shukor - Mohd Shukor, Nur Saufiah (2017)
Thesis submitted in fulfillment of the requirements for the degree of This study is carried out to identify the current laws and practices of the underage marriage system in Malaysia and whether the laws are adequate to provide protection to underage Muslim girls. Other than that, this study also examines underage marriage laws or norms as well as practices in Jordan and Morocco for a comparative analysis. Qualitative approach is adopted as a method to analyze the Islamic Family Law Federal Territories Act 1984 and other relevant laws as well as Syariah Court procedures regarding underage marriage. A semi-structured interview has been conducted with an academician with expertise in this area. The data showed that existing laws and procedures are not comprehensive enough to protect underage Muslim girls in Malaysia. This study has identified potential gaps in domestic legal system in providing protection for underage girls. Findings of this research show that underage marriage is not only about legal issue, but it is also a socioeconomic and sexual reproductive issue. Thus, this study proposes several promising legal and policy strategies to ensure the relevant authorities in making the best judgment regarding underage marriage applications. Perhaps it can be a guide, hence promoting and protecting the right of the girl child in Malaysia.